2020
DOI: 10.9734/arrb/2020/v35i830254
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Biology of Marine Catfish, Arius latiscutatus (Günther, 1864) and Arius gigas (Boulenger, 1911) from the Bays of Guinea

Abstract: Background and Objectives: Marine catfish are abundant in the bays of Tabounsou and Sangareah in Republic of Guinea, but the knowledge on their biology is still scanty. The reproductive biology of Arius latiscutatus Günther, 1864 and A. gigas Boulenger, 1911 was studied through monthly sampling, from January to December 2016. Methodology: Fish were caught using gill nets in several sampling sites. Five gonadal stages were described, based on macroscopic observation of gonad form, size, weight, color and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…According to these authors, the Ariidae would reach 40-42 cm at the age of 6 and the 80 cm individuals quite often caught by small-scale fisheries would be between 20 and 30 years old. In a recent study on the reproductive biology of Ariidae from two coastal bays of Guinea, Koivogui et al (2020) concluded that they had only one breeding season, during which coastal fisheries should be restricted to preserve the ability of broodstock renewal. Concerning estuarine areas, some aspects of the biology of Ariidae among other fish species were studied in the Sine Saloum estuary (Ecoutin & Albaret, 2003;Faye et al, 2012;Ndiaye et al, 2015;Panfili et al, 2006) and in the Gambia estuary (Ecoutin et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…According to these authors, the Ariidae would reach 40-42 cm at the age of 6 and the 80 cm individuals quite often caught by small-scale fisheries would be between 20 and 30 years old. In a recent study on the reproductive biology of Ariidae from two coastal bays of Guinea, Koivogui et al (2020) concluded that they had only one breeding season, during which coastal fisheries should be restricted to preserve the ability of broodstock renewal. Concerning estuarine areas, some aspects of the biology of Ariidae among other fish species were studied in the Sine Saloum estuary (Ecoutin & Albaret, 2003;Faye et al, 2012;Ndiaye et al, 2015;Panfili et al, 2006) and in the Gambia estuary (Ecoutin et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%